2014
DOI: 10.1098/rsif.2014.0467
|View full text |Cite
|
Sign up to set email alerts
|

A fish perspective: detecting flow features while moving using an artificial lateral line in steady and unsteady flow

Abstract: For underwater vehicles to successfully detect and navigate turbulent flows, sensing the fluid interactions that occur is required. Fish possess a unique sensory organ called the lateral line. Sensory units called neuromasts are distributed over their body, and provide fish with flow-related information. In this study, a three-dimensional fish-shaped head, instrumented with pressure sensors, was used to investigate the pressure signals for relevant hydrodynamic stimuli to an artificial lateral line system. Uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 31 publications
1
67
0
Order By: Relevance
“…They concluded that fish might be able to extract sensory information from complex stimuli like vortices by comparing the activity of a whole array of neuromasts A number of authors have established the feasibility of tracking vortices and vortical wakes: Yang et al (2006) for vortical wakes; Ren & Mohseni (2012) for regular or reverse Kármán vortex street using CN-like sensors distributed over the surface of a body, which provide sufficient information to extract the circulation of individual vortices, the wavelength of the Kármán street, the distance between the body and the fish h and the speed of propagation of the street. Likewise, Akanyeti et al (2011);Venturelli et al (2012); Salumae &Kruusmaa (2013), andChambers et al (2014) demonstrated using an array of pressure sensors that it is feasible to extract features from the flow such as the vortex shedding frequency, traveling speed, wake wavelength, and turbulence intensity. Fernandez et al (2011a) determined the strength and position of a free vortex pair translating near a streamlined body using sparse pressure sensor measurements and a potential flow model with an extended Kalman filter, comparing it to simultaneous PIV measuremnts.…”
Section: Tracking Swimming Fishmentioning
confidence: 99%
“…They concluded that fish might be able to extract sensory information from complex stimuli like vortices by comparing the activity of a whole array of neuromasts A number of authors have established the feasibility of tracking vortices and vortical wakes: Yang et al (2006) for vortical wakes; Ren & Mohseni (2012) for regular or reverse Kármán vortex street using CN-like sensors distributed over the surface of a body, which provide sufficient information to extract the circulation of individual vortices, the wavelength of the Kármán street, the distance between the body and the fish h and the speed of propagation of the street. Likewise, Akanyeti et al (2011);Venturelli et al (2012); Salumae &Kruusmaa (2013), andChambers et al (2014) demonstrated using an array of pressure sensors that it is feasible to extract features from the flow such as the vortex shedding frequency, traveling speed, wake wavelength, and turbulence intensity. Fernandez et al (2011a) determined the strength and position of a free vortex pair translating near a streamlined body using sparse pressure sensor measurements and a potential flow model with an extended Kalman filter, comparing it to simultaneous PIV measuremnts.…”
Section: Tracking Swimming Fishmentioning
confidence: 99%
“…Tiny hair cell bundles constitute the basic functional elements of all these sensors which translate mechanical stimuli into the electrical signals across the cell membrane [1,4,5]. The lateral-line system in fish and amphibians basically uses arrays of hair cell sensors for flow velocity and flow direction sensing [6,7] and the hair cells in limb joints of insects allow them to detect the orientation of their angled leg joints [8,9]. Despite the rich functionality and diversity in sensing applications, the fundamental sensing principle of all the biological hair cells is similar.…”
Section: Biological Hair Cell Sensors In Naturementioning
confidence: 99%
“…Previous studies investigated local flow fields that surround swimming fishes [35], spatial noise suppression by complex lateral line systems [36], bulk water flow sensing [37], spatial integration by canal structures [38], detection of Kármán vortex streets [39], dipole source localization [40,41], as well as hydrodynamic imaging [42][43][44][45]. However, in order not to influence the results through the presence of a measuring probe such as a hydrophone or a hot-wire anemometer, the evaluation of parameters has to be performed by means of mathematical modelling.…”
Section: Introductionmentioning
confidence: 99%